Economic freedom, post materialism and economic growth - Jordaan, Jacob A. (Social sciences & humanities open, 2023)
Whereas there is substantial evidence that economic freedom generates positive growth effects, much less is known about how social values impact the institutional framework underlying economic freedom. We address this gap in the literature, using panel data for a heterogeneous group of countries for the period 1980–2010 to examine whether post materialism influences the growth effect of economic freedom. Using instrumental variable estimation techniques within a three stages least square framework, we find that Fraser's economic freedom index and several of its components generate positive direct growth effects. Post materialism generates a negative direct growth effect. We also identify a positive indirect effect from post materialism that runs via economic freedom and its underlying components onto economic growth. These findings indicate that post materialism influences the institutional framework underlying economic freedom and that economic freedom acts as a transmission channel of economic effects of social values.